Incidence of medically attended influenza during pandemic and post-pandemic seasons through the Influenza Incidence Surveillance Project, 2009–13. Issue 9 (September 2015) - Fowlkes, Ashley; Steffens, Andrea; Temte, Jon; Lonardo, Steve Di; McHugh, Lisa; Martin, Karen; Rubino, Heather; Feist, Michelle; Davis, Carol; Selzer, Christine; Lojo, Jose; Oni, Oluwakemi; et al.
Summary Background Since the introduction of pandemic influenza A (H1N1) to the USA in 2009, the Influenza Incidence Surveillance Project has monitored the burden of influenza in the outpatient setting through population-based surveillance. Methods From Oct 1, 2009, to July 31, 2013, outpatient clinics representing 13 health jurisdictions in the USA reported counts of influenza-like illness (fever including cough or sore throat) and all patient visits by age. During four years, staff at 104 unique clinics (range 35–64 per year) with a combined median population of 368 559 (IQR 352 595–428 286) attended 35 663 patients with influenza-like illness and collected 13 925 respiratory specimens. Clinical data and a respiratory specimen for influenza testing by RT-PCR were collected from the first ten patients presenting with influenza-like illness each week. We calculated the incidence of visits for influenza-like illness using the size of the patient population, and the incidence attributable to influenza was extrapolated from the proportion of patients with positive tests each week. Findings The site-median peak percentage of specimens positive for influenza ranged from 58·3% to 77·8%. Children aged 2 to 17 years had the highest incidence of influenza-associated visits (range 4·2–28·0 per 1000 people by year), and adults older than 65 years had the lowest (range 0·5–3·5 per 1000 population). Influenza A H3N2, pandemic H1N1, and influenza B equally co-circulated in the first post-pandemic season, whereas H3N2 predominated for the next two seasons. Of patients for whom data was available, influenza vaccination was reported in 3289 (28·7%) of 11 459 patients with influenza-like illness, and antivirals were prescribed to 1644 (13·8%) of 11 953 patients. Interpretation Influenza incidence varied with age groups and by season after the pandemic of 2009 influenza A H1N1. High levels of influenza virus circulation, especially in young children, emphasise the need for additional efforts to increase the uptake of influenza vaccines and antivirals. Funding US Centers for Disease Control and Prevention.